2018
DOI: 10.1038/s41467-018-05868-0
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of the circadian gene Per1 contributes to age-related changes in hippocampal memory

Abstract: Aging is accompanied by impairments in both circadian rhythmicity and long-term memory. Although it is clear that memory performance is affected by circadian cycling, it is unknown whether age-related disruption of the circadian clock causes impaired hippocampal memory. Here, we show that the repressive histone deacetylase HDAC3 restricts long-term memory, synaptic plasticity, and experience-induced expression of the circadian gene Per1 in the aging hippocampus without affecting rhythmic circadian activity pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
131
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(146 citation statements)
references
References 66 publications
15
131
0
Order By: Relevance
“…Using enrichment network analysis after annotating the upregulated DEGs through the KEGG pathway database, we found that the most significant change occurred in the MAPK signaling pathway (also known as the Ras-Raf-MEK-ERK pathway) (Fig 3c). Circadian genes have recently been shown to be involved in hippocampus-dependent memory (56,57), and the lack of functional Per1 in the hippocampus impairs object location memory (58) and LTP (59). As predicted, based upon the downregulation of circadian pathways we observed after learning in CBP KIX/KIX mice, we also found pathways related to circadian rhythm and circadian entrainment to be upregulated following spatial learning in WT mice.…”
Section: Spatial Learning Induces Cbp Downstream Genes In Wt Micesupporting
confidence: 79%
See 1 more Smart Citation
“…Using enrichment network analysis after annotating the upregulated DEGs through the KEGG pathway database, we found that the most significant change occurred in the MAPK signaling pathway (also known as the Ras-Raf-MEK-ERK pathway) (Fig 3c). Circadian genes have recently been shown to be involved in hippocampus-dependent memory (56,57), and the lack of functional Per1 in the hippocampus impairs object location memory (58) and LTP (59). As predicted, based upon the downregulation of circadian pathways we observed after learning in CBP KIX/KIX mice, we also found pathways related to circadian rhythm and circadian entrainment to be upregulated following spatial learning in WT mice.…”
Section: Spatial Learning Induces Cbp Downstream Genes In Wt Micesupporting
confidence: 79%
“…Recent evidence suggests that circadian rhythm disruptions may contribute to increased risk or aggravate disease pathology for neurodegenerative diseases including Alzheimer's disease and Parkinson's disease (106)(107)(108)(109)(110)(111). Additionally, recent research suggests that hippocampal Per1 specifically may be critical to age-related cognitive impairments (58). The CBP KIX domain appears to represent a potential target for understanding the effects of circadian and memory impairments that occur with aging.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic phase relationships of molecular clock components outside the SCN have yet to be explored but may be important for subsequent physiological changes. For example, acquisition of object location memory induces Per1 expression in hippocampus, and Per1 induction is required for long‐term memory formation (Kwapis et al., ). Given the complex circuitry in each brain region, the phase and coupling strength of the molecular clock in specific cell types is also likely to affect electrical activity and thus, circuit function.…”
Section: Conclusion: Areas Of Future Investigationmentioning
confidence: 99%
“…Although young C57BL/6J mice reliably show robust long‐term memory following a 10‐min OLM training session (Kwapis et al., ; McQuown & Wood, ; Vogel‐Ciernia et al., ; Current Protocols article: Vogel‐Ciernia & Wood, ), other strains and ages may need more training. For example, we have previously shown that OLM is impaired in 18‐month‐old C57BL/6J mice (Kwapis et al., ). In order to study memory updating in these mice, we increased the amount of training from one 10‐min session to three 10‐min sessions (one session per day for 3 days) and verified that old mice successfully learn the original object locations under this increased training protocol (Kwapis et al., ).…”
Section: Commentarymentioning
confidence: 99%